Effect of high pressure homogenization (microfluidization) on the quality of Ottoman Strawberry (F. Ananassa) juice. Issue 2 (December 2015) - Karacam, Cagrı Helin; Sahin, Serpil; Oztop, Mecit Halil
Abstract In this study, effect of high pressure homogenization (HPH) on the physical and chemical properties of Ottoman Strawberry juice was investigated. The juice was processed at two different pressures (60 MPa and 100 MPa) with two different passes (2 and 5 passes). Antioxidant activity, total phenolic content (TPC), mean particle size, color, viscosity and total soluble solid content of the samples homogenized with different passes and pressures were evaluated. Mean particle size and CIE L*a*b* color values of the juice showed significant difference (p < 0.05) at both pressures. While antioxidant activity and TPC of the juice did not change significantly (p > 0.05) at 60 MPa, significant difference was found at 100 MPa. For 60 MPa, total soluble solid content of the juice changed significantly (p < 0.05) whereas no change on total soluble solid content was observed at 100 MPa (p > 0.05). The results indicated that HPH could be used to improve the physical and chemical properties in the Ottoman Strawberry juice, such as increasing TPC, antioxidant activity and affecting color positively resulting in a desirable high quality juice for the consumer.